The Networks of Faith and Politics: Exploring Santri Electoral Behavior in Central Java Elections 2024 - Abdulrahman, Wahid; Lailiyah, Nuriyatul (JPW (Jurnal Politik Walisongo), 2025)
The presence of Islamic boarding school students (santri) in Indonesia’s political history holds substantial significance, not merely due to their growing demographic weight but also because of their strategic influence and pivotal roles in the last three national elections. Santri function not only as active voters but also as critical components of electoral coalitions and, in some cases, as candidates themselves. This study employs a quantitative research design utilizing a multistage random sampling technique, with a margin of error of 3.1%, a 95% confidence level, and an assumed population variance of 50:50, resulting in a sample size of 1,076 respondents. Data were collected through structured face-to-face interviews conducted during the 2024 general elections in Central Java. Participants comprised individuals who had attended and resided in Islamic boarding schools (pesantren). Findings indicate that family members and religious leaders exert a strong influence on santri's political engagement. A majority of santri report still relying on family networks and religious authorities as primary reference points when selecting their preferred candidates. Furthermore, the majority of santri are affiliated with the Nahdlatul Ulama (NU) organization, which remains a dominant institutional force within Indonesia’s Muslim community. However, the alignment between santri and formal political parties, especially Islamic political parties, remains relatively fluid, with only a minority holding formal party membership or sustained political affiliations. This suggests that while religious identity shapes political values, party loyalty among santri is neither uniform nor necessarily strong.